Perlindungan Hukum Terhadap Pelanggaran Hak Cipta Melalui Internet - Asmaul Asmaul; Kairuddin Karim; Lia Trizza Firgita Adhilia (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This research was conducted aiming to find out the forms of copyright infringement that are carried out via the Internet and to find out the government's legal protection for copyright holders of songs on cassettes and compact disks whose copyrights are infringed via the Internet. The type of research used in this research is normative research. The results of the study show that Intellectual Property Rights, especially in the field of Copyright, are recognized by the existence of Law Number 28 of 2014 concerning Copyright which is used as a tool to protect ideas and new works by the Indonesian people. Under the law, copyright falls under Intellectual Property Rights (IPR), including patents, industrial design rights, trademark rights, integrated circuit layout design rights, and trade secret rights. There are several forms of copyright infringement on the internet, including creating websites for famous singers containing their songs, then creating sites containing songs from famous singers, there is also spreading videos of singers by uploading videos of these singers to Youtube sites without the knowledge of the singer or the owner of the singer's record label. As well as copyright protection with the existence of Law Number 28 of 2014 concerning Copyright, it contains a minimum and maximum amount of punishment that can be received by copyright violators, whether in the form of imprisonment or fines.